Lipoprotein Particles Interact with Membranes and Transfer Their Cargo without Receptors - Plochberger, Birgit; Sych, Taras; Weber, Florian; Novacek, Jiri; Axmann, Markus; Stangl, Herbert; Sezgin, Erdinc (Biochemistry (Easton), 2020)
Lipid transfer from lipoprotein particles to cells is essential for lipid homeostasis. High-density lipoprotein (HDL) particles are mainly captured by cell membrane-associated scavenger receptor class B type 1 (SR-B1) from the bloodstream, while low-density and very-low-density lipoprotein (LDL and VLDL, respectively) particles are mostly taken up by receptor-mediated endocytosis. However, the role of the target lipid membrane itself in the transfer process has been largely neglected so far. Here, we study how lipoprotein particles (HDL, LDL, and VLDL) interact with synthetic lipid bilayers and cell-derived membranes and transfer their cargo subsequently. Employing cryo-electron microscopy, spectral imaging, and fluorescence (cross) correlation spectroscopy allowed us to observe integration of all major types of lipoprotein particles into the membrane and delivery of their cargo in a receptor-independent manner. Importantly, the biophysical properties of the target cell membranes change upon delivery of cargo. The concept of receptor-independent interaction of lipoprotein particles with membranes helps us to better understand lipoprotein particle biology and can be exploited for novel treatments of dyslipidemia diseases.
Keywords: lipidové dvojvrstvy; Microscopy, Atomic Force; Biological Transport; biologický transport; mikroskopie atomárních sil; lipoproteiny; Cell Membrane; Lipid Bilayers; buněčná membrána; Lipoproteins